1998
DOI: 10.1002/(sici)1097-4628(19981003)70:2<389::aid-app20>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Properties of poly(ethylene terephthalate) and maleic anhydride-grafted polypropylene blends by reactive processing

Abstract: The properties of poly(ethylene terephthalate) (PET) and polypropylene (PP) blends and PET/maleic anhydride-grafted PP (MAgPP) reactive blends were investigated. Two blend systems were immiscible based on tan ␦ measured by dynamic mechanical analyzer (DMA). In case of PET/MAgPP blends, the reaction of ester groups of PET and MA sites on MAgPP occurred during melt mixing at 280°C for 30 min. The reaction was confirmed by a new peak between the glass transition temperatures of PET-rich and MAgPP-rich phase on ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 14 publications
0
16
0
3
Order By: Relevance
“…Their result shows that the finest PET domain was at 10 wt% of PP‐g‐MAH. The reaction of ester groups of MAH with the PET/PP blends during melt mixing increased the tensile strength, tensile modulus, and elongation at break of the blends . Champagne et al have studied PET/PP blends compatibilized with PP grafted glycidyl methacrylate and observed that the use of the modifier changed the tensile behavior from fragile to ductile, increased the tensile strength by 10%, and improved elongation at break by 10 to 20‐fold.…”
Section: Introductionmentioning
confidence: 99%
“…Their result shows that the finest PET domain was at 10 wt% of PP‐g‐MAH. The reaction of ester groups of MAH with the PET/PP blends during melt mixing increased the tensile strength, tensile modulus, and elongation at break of the blends . Champagne et al have studied PET/PP blends compatibilized with PP grafted glycidyl methacrylate and observed that the use of the modifier changed the tensile behavior from fragile to ductile, increased the tensile strength by 10%, and improved elongation at break by 10 to 20‐fold.…”
Section: Introductionmentioning
confidence: 99%
“…And yet, polymer/graphene masterbatch during preparation still did not completely avoid the use of organic solvents. To solve this problem, reactive extrusion can provide a good way for the preparation of graphene/polymer masterbatch, which has been widely used for the industrial synthesis of polyolefin grafted polyester copolymers by melt phase processing …”
Section: Introductionmentioning
confidence: 99%
“…Polyethylene terephthalate (PET) and polypropylene (PP) are known to be fully immiscible and require interfacial modification to obtain good emulsification and to increase the solid‐state adhesion. Numerous investigations have been performed to compatibilize PET and PP with different types of compatibilizer containing maleic anhydride (MA), acrylic acid, or glycidyl methacrylate functionality 13–17. The incorporated compatibilizer decreases the interfacial tension between PET and PP, thus leading to a finer morphology of the blends 18.…”
Section: Introductionmentioning
confidence: 99%